RNA transport during TMV cell-to-cell movement - Peña, Eduardo José; Heinlein, Manfred (Frontiers in Plant Science, 2012)
Studies during the last twenty-five years have provided increasing evidence for the ability of plants to support the cell-to-cell and systemic transport of RNA molecules and that this process plays a role in plant development and in the systemic orchestration of cellular responses against pathogens and other environmental challenges. Since RNA viruses exploit the cellular RNA transport machineries for spreading their genomes between cells they represent convenient models to investigate the underlying mechanisms. In this regard, the intercellular spread of Tobacco mosaic virus (TMV) has been studied for several years. The RNA of TMV moves cell-to-cell in a non-encapsidated form in a process depending on virus-encoded movement protein (MP). Here, we discuss the current state of the art in studies using TMV and its MP as a model for RNA transport. While the ability of plants to transport viral and cellular RNA molecules is consistent with RNA transport phenomena in other systems, further studies are needed to increase our ability to visualize viral RNA in vivo and to distinguish RNA-transport related processes from those involved in antiviral defense.